Effect of Supplementations of Comin+ and Zn-biocomplex on the performances of Ettawa Crossbred goats - Supriyati .; W Puastuti; I-G.M Budiarsana; I-K Sutama (Jurnal Ilmu Ternak dan Veteriner, 2012)
Digestibility of ruminant feeds is greatly determined by ruminal fermentation which in turn is greatly affected by micro-ecology of the rumen. Manipulation of micro-ecology such as supplementing with various yeasts or micro elements could improve digestibility of the feed. The effect of Comin+ (R1) and Zn-biocomplex (R2) alone or their combination (R3) on performance of Ettawa Crossbred kids, fed concentrate containing Aspergillus oryzae (R0) was studied. Twenty four Ettawa Crossbred kids (6-8 month of age; initial liveweights =16.63±2.10 kg) were divided into 4 groups. Feeds given were King grass (Pennicetum purpuroides) ad libitum and concentrate. The observations were carried out for 16 weeks with 2 weeks adaptation period and the experiment was conducted in a completely randomized design with 4 treatments and 6 replications. The results showed that supplementations significantly (P < 0.05) increased total DM intakes from 685 g/d (R0) became 748, 711 and 858 g/d; and grass DM intakes from 304 g/d (R0) became 373, 331 and 479 g/d for R1, R2 and R3, respectively. Digestibilities of DM, NDF and DE/GE were not affected by supplementation, but supplementations significantly (P < 0.05) affected digestibilities of ADF and CP. Supplementation also significantly improved (P < 0.05) ADG from 65.18 g/d (R0) became 94.64, 83.04 and 90.77 g/d; and FCR from 10.51 (R0) became 7.82, 8.36 and 9.46 for R1, R2 and R3, respectively. It was concluded that supplementation of Comin+ (R1) gave the best growth performance of Ettawa Croosbred goats, where ADG and FCR improved by 45.20% and 34.40%. Key Words: Supplementation, Comin+ , Zn-biocomplex, Performances, Goats